Determinantes da liquidez de corporate bonds no mercado brasileiro - Gesualdo Neto, Osmar (2015)
The aim of this thesis is to investigate the Brazilian corporate bonds’ secondary market, to answer what features of the bonds affect its liquidity and the liquidity characteristics which can be observed in Brazilian corporate bonds. Five liquidity measures were used: number of days that occurred transactions, number of transactions, transactions volume compared to the amount issued, price spread traded daily and yield volatility. For each measure of liquidity, the influence of eight characteristics of the Brazilian corporate bonds was found: rating issued volume, maturity, issuer sector, listed on the stock exchange, issued age and issue type (encouraged and under instruction restricted efforts). There are collected 998 public debentures and their respective transactions up to 18 months after issue, from January 2007 to August 2015. The database, which totaled 53,085 observations, was based on market prices supplied daily by the Brazilian National Debentures System. As a result, it was found that issue volume, issue type (encouraged or restricted) and certain segments are liquidity variables. Additionally, it was found that, by controlling the segments of issuing, bonds with the highest volume are given more liquidity. Moreover, the relationship between age and liquidity is not clear and price spread traded daily is not an adequate liquidity measure. Finally, it was found that the high concentration of securities issued under restricted efforts reduced market liquidity compared to the study of Sheng and Saito (2008), despite the increase in the issued volume in the period. By contrast, the issuance of bonds encouraged raised the level of transactions in the secondary market.